ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN KONSUMEN DI TOKO DUTA FLORA NURSERY - Citrawan, Cendikia; Tigor, Ryan Hasianda; Oktalina, Gayatria (Jurnal Progresif Manajemen Bisnis, 2023)
The purpose of this research is to analyze, Product Quality, Service Quality and Location on Customer Satisfaction either partially or simultaneously. The theories used in this research are management theory, marketing theory, marketing management theory, product quality, service quality, location and customer satisfaction. The method used in this research is descriptive with a quantitative approach with a view to finding the relationship between research variables using statistical formulas. While the statistical formula used to test the hypothesis is Multiple Linear Regression Analysis. The sample in this study amounted to 96 people. The results of the study proved that: (1) product quality affects consumer satisfaction, (2) service quality affects consumer satisfaction. (3) location affects customer satisfaction